Variability of Permafrost and Landscape Conditions Following Clear Cutting of Larch Forest in Central Yakutia. (2nd June 2016) - Fedorov, Alexander N.; Iwahana, Go; Konstantinov, Pavel Y.; Machimura, Takashi; Argunov, Radomir N.; Efremov, Peter V.; Lopez, Larry M.C.; Takakai, Fumiaki
Abstract: Permafrost landscape dynamics were investigated between 1998 and 2012 at Neleger, near Yakutsk, in central Yakutia, to determine the effects on permafrost of clear cutting of larch forest. Changes in ground temperature, soil moisture, seasonal thaw depth and surface subsidence at a control (forest) site and a site cleared of forest were associated with vegetation recovery and climate change. Before clear cutting (1998–2000), permafrost temperatures were similar to the 1998–2012 average. After cutting (2001–04), permafrost temperatures decreased in the undisturbed forest site, but increased in the cleared site. The thermal disturbance of clear cutting caused increases in thaw depth and led to 4.8 cm of ground surface subsidence. Significant warming of permafrost in 2005–08, coincident with maximum snow depth and precipitation, caused up to 14.6 cm of additional ground subsidence, which represented the maximum changes observed in the landscape. Between 2009 and 2012, permafrost began to stabilise and subsidence was restricted to 1.8 cm. The reduced thaw depth and the growth of young birch shoots during this period indicated stabilisation of permafrost conditions and the beginning of landscape restoration. Copyright © 2016 John Wiley & Sons, Ltd.